.Effect of fermentation of poultry fertilizer and spraying of Tecamin Max in the vegetative growth characteristics of the Solanum tuberosum L potato - Al - Hamdani, Sabeeh Abdul Wahab; Al-Janabi, Muhammad Ali Abboud; Al-Azzawi, Ghazwan Salem Muhammad (Journal of agricultural, environmental and veterinary sciences, 2017)
A field experiment was carried out at the research station of the Department of Horticulture and Garden Engineering at the Faculty of Agriculture, University of Diyala, in the autumn season of the 2016 agricultural season where the tubers were grown on 8/9/2016 in a soil with a green mix. The locally produced Burren potato tubers were used from the previous spring loop Super Elite), in order to study the effect of fermentation of poultry fertilizer and spray with Tecamin Max in the growth and yield of potatoes, as the experiment included fifteen treatment of the mixture is a combination of five levels of organic fertilizer fermented and non-fermented 0, without adding, 3% and 6% fertilizer Fermented and 3% and 6% non-fermented fertilizer of soil size (measured on a (F0, F1, F2, F3 and F4) respectively, three levels of Tecamin Max and concentrations 0, 2 and 4 mL L-1 and its symbol T0, T1 and T2) respectively, the coefficients were distributed in a three-piece vertical experiment on the irrigation line to ensure that irrigation water was distributed evenly and by randomized complete block design (RCBD). The most important results can be summarized as follows: • The addition of fertilized poultry fertilizer to the soil by 6% (F2) resulted in a significant increase in plant height, number of air legs, leg diameter, area of paper and total chlorophyll content. • Spraying of Tecamin Max at 4 mL L-1 (T2) significantly increased the length of the plant, the number of main air stems, calf diameter and leaf content of total chlorophyll, while the T1 spray treatment exceeded the area of the single paper.